THE PROBLEM OF PRIMARY AND SECONDARY LEVELS, THE DIFFERENCE BETWEEN LANGUAGE AND SPEECH - Eshmonov Otabek Usanovich (Bright Mind Publishing, 2025)
It is very important to take into account these distinctions when considering the language and speech units. There are some conceptions according to which the terms of "language levels" are substituted by the term of "emic level" while the "speech levels" are substituted by "ethic levels". Very often these terms are used interchangeably. The lowest level in the hierarchy of levels has two special terms: phonology and phonetics. Phonology is the level that deals with language units and phonetics is the level that deals with speech units. The lowest level deals with language and speech units which are the smallest and meaningless.
Keywords: Wide - spread opinion, phonemes, morphemes, lexemes, word -combinations (phrases).